Willingness to accept Doxycycline post-exposure prophylaxis for bacterial stis prevention among men who have sex with men in Southern China: a cross-sectional analysis - Liang, Peng; Zhao, Peizhen; Huang, Shujie; Wang, Cheng (BMC infectious diseases, 2025)
Doxycycline post-exposure prophylaxis (doxy-PEP) has the potential to decrease the incidence of sexually transmitted infections (STIs) among men who have sex with men (MSM). However, there is a limited literature on willingness to use doxy-PEP among Chinese MSM. This study aimed to examine the willingness to use doxy-PEP and its associated factors among MSM in China. In 2023, we conducted a cross-sectional study in four cities in Guangdong provinces in South China. Data were collected on social-demographic characteristics, sexual behaviors, and the willingness to use doxy-PEP. Multivariable logistic regression analysis was employed to identify factors associated with the willingness to use doxy-PEP. A total of 884 individuals were included in this study. Of these, 53.5% reported a willingness to use doxy-PEP for the prevention of STIs. The main concerns for those unwilling to use doxy-PEP were related to its efficacy (82.5%) and safety (81.7%). Multivariable logistic regression indicated that participants were more likely to express willingness to use doxy-PEP if they had female sexual partners in the past 6 months (adjusted Odds Ratio (aOR): 1.58, 95% CI: 1.11-2.25), had prior or current doxy-PEP use (aOR = 2.39, 95% CI: 1.13-5.05), or had peers currently using doxy-PEP (aOR = 1.58, 95% CI: 1.09-2.30). The willingness to use doxy-PEP among MSM in South China is relatively low. These findings highlight the need for effective educational and targeted intervention strategies to raise awareness and knowledge toward using doxy-PEP among MSM in China.